Investigating Pre-service Mathematics Teachers' Innovation Awareness and Views Regarding Intelligent Tutoring Systems - Erdemi̇r, Mustafa; İnğeç, Şebnem (Horizon Research Publishing Co., Ltd., 2016)
The purpose of this study is to identify pre-service primary mathematics teachers' views regarding on Web-based Intelligent Tutoring Systems (WBITS) in relation to its usability and influence on teaching. A survey method was used. The study was conducted with 43 students attending the mathematics teaching program under the department of elementary education. The data were collected through a paper-based survey composed of three parts. In the first part of the survey, there are 9 items about demographic information demographic profile of the respondents such as name, gender, age, study styles, learning styles, and motivation styles. In the second part, there is a scale about "Innovation Awareness Scale" and in the third part there is a scale about views concerning the usability and the influence of WBITS on learning. The data obtained from the study were analyzed using SPSS-21 based on descriptive statistics such as frequency, percentage distribution, and arithmetic mean in addition to MANOVA, which is a parametric test, and "Pearson product-moment correlation coefficient". Analysis indicated that the participants were "neither negative or positive" regarding both WBITS and innovation. It was seen that there was no significant relationship between participant awareness regarding innovation and their views regarding WBITS. Another important finding is that study styles, learning styles, and motivation styles are not influential variables over their views about WBITS' usability and its effect on learning attitudes towards WBITS.
Keywords: 4. Education